The Effects of Globalization on India: Exploring the Transformative Effects of Globalization on India and its Governance (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Globalization is simply a process of intensification and expansion of political interrelations across the globe. The affair is the outcome of the expenditure, outsourced manufacturing and international trade. This whole concept is supported by information technology, with the aim of bringing economies of various countries together. It can be called a doorway through which people, goods and services get to move freely across the Globe, it is through the process of globalization that every individual field is witnessing a huge smash on cultural, social, monetary, political, and communal life of Individuals living in every part of the world. With the introduction of globalization we are witnessing the emergence of a concept which we can call as Global Governance.